Strategic Recommendations for Establishing an Undergraduate Biomedical Science Program in Indonesia: A Narrative Review of Curriculum, Infrastructure, Human Resources, and Partnerships - Arfira, Fathiya Rahma; Nadiiyah, Salma; Zahroya, Isvina Unai (Jurnal Penelitian Inovatif, 2026)
The post-pandemic era has heightened the need for biomedical scientists in Indonesia, encouraging universities to expand and establish undergraduate Biomedical Science (BMS) study programs. However, rapid program development without adequate strategic preparation may result in challenges such as poorly aligned curricula, insufficient laboratory infrastructure, and limited institutional capacity. This narrative review identifies key considerations for developing academically sound and sustainable programs. A literature search was conducted using databases such as PubMed and Scopus, alongside national and international institutional guidelines (LAM-PTKes, KKNI, QAA, IFBLS) published between 2015 and 2026. Data were synthesized to formulate strategic recommendations categorized into four principal components: curriculum design, laboratory infrastructure, human resources, and strategic partnerships. Key findings emphasize the necessity of defining a distinct scientific niche and structuring an outcome-based curriculum that strictly distinguishes BMS from generic medicine, pharmacy or biology degrees by emphasizing laboratory-based and translational competencies. Furthermore, institutions must secure dedicated, specialized laboratory infrastructure prior to program launch and not rely primarily on repurposed or shared general science facilities. Successful implementation also depends on recruiting a multidisciplinary core faculty and competent laboratory technical staff capable of supporting teaching and research activities. Finally, finalizing collaborative agreements with clinical and industrial stakeholders is required to ensure authentic work-based learning and continuous curriculum evaluation. Adhering to these synthesized guidelines helps universities to strengthen accreditation readiness and support the development of competent biomedical science graduates who are equipped to contribute to Indonesia’s evolving healthcare, research, and biomedical sectors.